Comparative assessment of the efficacy of closed helical loop and T-loop for space closure in lingual orthodontics-a finite element study - Ajay Chacko; Tripti Tikku; Rohit Khanna; Rana Pratap Maurya; Kamna Srivastava (SpringerOpen, 2018)
Abstract Background Retraction in lingual orthodontics has biomechanical differences when compared to labial orthodontics, which is not yet established. Thus, we have intended to compare the biomechanical characteristics of closed helical loop and T-loop on 1 mm activation with 30° of compensatory curvatures during retraction in lingual orthodontics. Methods STb lingual brackets were indirectly bonded to maxillary typhodont model that was scanned to obtain FEM model. Closed helical loop (2 × 7 mm) and T-loop (6 × 2 × 7 mm) of 0.016" × 0.016" TMA wire were modeled without preactivation bends. Preactivation bends at 30° were given in the software. Boundary conditions were set. The force (F) and moment (M) of both the loops were determined on 1 mm activation, using ANSYS software. M/F ratio was also calculated for both the loops. Results T-loop exerted less force, thus increased M/F ratio as compared to closed helical loop on 1 mm activation. Conclusions When torque has to be preserved in the anterior segment during retraction in lingual orthodontics, T-loop can be preferred over closed helical loop.